Organizational Change, Leadership and Ethics Leading Organizations towards Sustainability - By, Rune; Burnes, Bernard; Hughes, Mark (Routledge Studies in Organizational Change & Development, 2023)
Organisations and societies are facing extreme challenges that require action (IPCC, 2021). The UN's sustainability goals, demographic change, and the green shift are knocking on the door, while traditional education, and ways of leading and managing this development, often fail to keep up. Organizational Change, Leadership and Ethics challenges leadership orthodoxy, assumptions, and myths currently preventing the further development of theory and practice. It encourages intelligent disobedience in support of greater leadership capabilities and capacity in organisations and societies. As such the book is written for everyone who want be MAD - to Make A Difference - students, scholars, and practitioners alike.